Magnetic resonance imaging of a giant frontal hemorrhagic mucocele with intracranial extension in a cat. Issue 5 (21st June 2018) - Vandenberghe, Hélène; Thibaud, Jean‐Laurent; Moissonnier, Pierre; Blot, Stéphane
Abstract: A 6‐year‐old domestic short‐haired cat was presented with an acute onset of right cortical encephalopathy. Magnetic resonance imaging (MRI) performed 4 days after the onset of clinical signs revealed a lesion originating from the right frontal sinus with intracranial extension and compression of the right frontal lobe. The lesion was T1‐weighted hypointense and T2‐weighted and fluid‐attenuated inversion recovery hyperintense. Signal voids within the lesion were observed on T2* images, consistent with hemorrhage. Peripheral ring enhancement was visible on postcontrast sequences. These features were consistent with a giant hemorrhagic mucocele. To the authors' knowledge, this is the first report of MRI characteristics of this lesion in a cat.